Мини- и микро ЭВМ семейства " Электроника" - Толстых Б. Л. Борис Леонтьевич; Талов И. Л. Игорь Леонидович; Цывинский В. Г. Владимир Георгиевич; Межов В. Е. (Москва, Радио и связь, 1987)
Исключено из фонда НТБ ТПУ